Model Illustrates the Relationships and Impacts of Using Sustainable Agricultural Practices to Empowerment Farmers Case Study in Indonesia - Pramono Hadi; Suwardi Suwardi; Firstnandiar Glica Aini S (Journal of Innovative and Creativity, 2025)
This study explores the relationships and impacts of sustainable agricultural practices on the empowerment of farmers in Indonesia, farmers experience improvements in environmental sustainability, productivity, and socio-economic well-being. A case study approach was applied in various regions of Indonesia, utilizing qualitative and quantitative data collected through interviews, focus group discussions, and field observations. The findings reveal that sustainable farming practices significantly contribute to soil health, biodiversity, and reduced chemical dependency, while also enhancing farmers' knowledge, skills, and income through training, community engagement, and support programs. Initiatives led by government policies, community-based organizations, and corporate social responsibility programs have further strengthened farmer empowerment. The study concludes that sustainable agriculture not only improves agricultural productivity but also promotes equitable and resilient rural development across Indonesia.